Trophic influences on survival, development and reproduction of Hyperaspis notata (Col., Coccinellidae) - Staubli Dreyer, B.; Neuenschwander, Peter; Baumgaertner, J.U.; Dorn, S. (Wiley, 1997)
The coccinellid, Hyperaspis notata Mulsant, is associated with the mealybugs Phenacoccus manihoti Mat.‐Ferr. and P. herreni Williams, on cassava in southern Brazil and the highlands of Colombia. Brought to Africa to help control the accidentally introduced P. manihoti, its range of target prey and plant food sources as well as its performance under conditions of food scarcity were investigated in the laboratory. H. notata showed a moderately narrow food spectrum which should allow survival in periods when P. manihoti is scarce without threatening a broad range of insects species: H. notatasurvived, completed larval development and reproduced on P. madeirensis(Green) and Ferrisia virgata (Cockerell), which are alternate prey species of the family Pseudococcidae and occur abundantly in cassava fields and on ornamental plants in southern Benin. By contrast, development was not possible on less related taxa of the Sternorrhyncha, namely on Aphis craccivoraKoch which occur on cowpea often intercropped with cassava and on the spiralling white fly Aleurodicus dispersus Russel infesting cassava, and many other food crops and ornamental plants. These alternate food sources allowed survival of the larvae and adults for a limited period only and neither moulting nor egg production were observed. Cassava pollen was unsuitable as a food source since it did not allow larvae to develop, females to oviposit, nor did it extend longevity of larvae and adults. Honey prolonged the life span of adults without allowing egg production, and is thus a suitable food substitute for adult H. notata during shipment to release destinations. The coccinellid larvae completed their development to the adult stage when fed from a range of ad libitum supply (consuming up to 6 mg per day) of cassava mealybugs to a minimal daily amount of 1 mg (consuming only ∽0.8 mg per day). Females even laid eggs when fed with a minimal amount of 1.2 mg per couple and day. Larvae of the Colombian strain gained more weight before pupation, and the tolerance of larvae and adults to starving was more marked than in the Brazilian strain.